TE WA WHAKAPAOHO ITE REO IRIRANGI: Some Directions in Maori Radio. (3rd October 2015) - Wilson, Helen
Abstract : The bicultural policies of much of the public sector in Aotearoa/New Zealand are based on the Treaty of Waitangi.Broadcasting is taken by many Maori to be an important means of empowerment, especially with regard to cultural revival and language maintenance. In the field of broadcasting there have been three major cases before the Waitangi Tribunal. The Te Reo Maori Report (1986) identified the Maori language as a valued possession which the Crown ought to have protected. This looks at the state of Maori radio.